2022
DOI: 10.1016/j.xphs.2021.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Insoluble Particulate Matters in Therapeutic Protein Injections Using Light Obscuration and Flow Imaging Methods

Abstract: Quantitative evaluation of insoluble particulate matters in therapeutic protein injections using light obscuration and flow imaging methods.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The FlowCam is a relatively new instrument that is beginning to be used to accelerate the morphological analysis of particles and microorganisms but has yet to be widely employed in the field of colloidal synthesis. [28][29][30][33][34][35][36][37][38][39] The FlowCam uses flow imaging microscopy for the rapid acquisition of particle images, in conjunction with VisualSpreadsheet 6 software for rapid analysis of 39 geometric parameters (e.g., edge gradient, length, width, aspect ratio). Flow imaging microscopy digitally captures particles by streaming a particle-containing liquid through a microscope.…”
Section: Resultsmentioning
confidence: 99%
“…The FlowCam is a relatively new instrument that is beginning to be used to accelerate the morphological analysis of particles and microorganisms but has yet to be widely employed in the field of colloidal synthesis. [28][29][30][33][34][35][36][37][38][39] The FlowCam uses flow imaging microscopy for the rapid acquisition of particle images, in conjunction with VisualSpreadsheet 6 software for rapid analysis of 39 geometric parameters (e.g., edge gradient, length, width, aspect ratio). Flow imaging microscopy digitally captures particles by streaming a particle-containing liquid through a microscope.…”
Section: Resultsmentioning
confidence: 99%
“…3 Biomolecular Measurement Division, National Institute of Standards and Technology, Gaithersburg, MD, USA. * email: Scott.Lute@fda.hhs.gov; Ashwinkumar.Bhirde@fda.hhs.gov been reported that LO typically underestimates the counts and sizes of proteinaceous particles as these values are significantly influenced by the optical property of a sample [9][10][11] . MM systems can render particle images and morphological data along with particle counts, however, chemical identification of the particles is not possible 12,13 .…”
mentioning
confidence: 99%
“…Unlike the post-filtration analysis of MM, MDRS can evaluate the SVP in their native state, avoiding distortion of soft proteinaceous particles. In addition, previous high-throughput particle analysis studies have focused on particle quantitation and conducted particle identification solely depending on their images [9][10][11][12][13] . Our findings show that along with detailed morphological information, MDRS provides chemical identification of individual particles, which is more definitive approach.…”
mentioning
confidence: 99%